Synthesis and characterization of luminescent SiO2@Eu(phen–Si) core–shell nanospheres. (20th November 2019) - Li, Wen‐Xian; Zheng, Yu‐Shan; Zhang, Hong‐Bo; Bao, Jin‐Rong; Li, Yi‐Lian; Ma, Yang‐Yang; Feng, Li‐Na; Feng, Shu‐Yan
Abstract: Four core–shell structured nanometre luminescent composites with different kernel sizes and different shell layer thicknesses (SiO2(500) @Eu (phen–Si)(50), SiO2(500) @Eu (phen–Si)(15), SiO2(250) @Eu (phen–Si)(5) and SiO2(250) @Eu (phen–Si)(10) ) were made by changing synthesis conditions. Here, initial subscript numbers in parentheses refer to the particle size of the SiO2 core, whereas the final subscript numbers in parentheses refer to shell layer thickness. In these composites, silica spheres of 500 nm or 250 nm were identified as the core. The shell layer was composited of silicon, 1, 10‐phenanthroline and europium perchlorate, abbreviated as Eu(phen–Si); the chemical formula of phen–Si was phen‐N‐(CONH (CH2 )Si(OCH2 CH3 )3 )2 . The composites were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and infrared spectroscopy. The monodispersed spherical SiO2 showed characteristics of a regular microstructure and a smooth surface, as well as the advantage of dispersity, shown by SEM. The Eu(phen–Si) complex was able to self‐assemble into monodispersed SiO2 spheres, as seen using TEM. Fluorescence spectra indicated that the four composites had excellent luminescence properties. Furthermore, composites composed of a SiO2 core and a 250 nm kernel size exhibited stronger fluorescence than 500 nm kernel‐sized composites. Fluorescence properties were affected by shell thickness: the thicker the shell, the greater the fluorescence intensity. For the four composites, quantum yield values and fluorescence lifetime corresponded to fluorescence emission intensity data as quantum yield values and fluorescence lifetime were higher, and luminescence properties increased.